Metallogenic age and hydrothermal evolution of the Huangyangshan graphite deposit in eastern Xinjiang, NW China: constraint from zircon geochronology and geochemistry - Sun, Xinhao; Ren, Yunsheng; Sun, Zhenjun; Li, Jingmou; Huang, Mengjia (Frontiers in Earth Science, 2026)
The Huangyangshan graphite deposit in the East Junggar region of Xinjiang Province is the world’s first documented graphite deposit hosted within an alkaline granite intrusion. Classified as fluid-deposited graphite deposit, it exhibits features of both magmatic and hydrothermal deposits, thus holding special significance for theoretical research. In this study, we conducted LA-ICP-MS zircon U-Pb dating and trace element analyses on zircons from the Huangyangshan deposit orebodies. And comprehensive analysis has been conducted on the REE geochemical signatures of the youngest fine-grained biotite granite within the Huangyangshan pluton. Based on their textures and element compositions, zircons can be divided into two types. Type I zircons are pale, large-grained, with clear oscillatory zonation, low Th, U, and REE contents, and significant positive Ce and strong negative Eu anomalies, which can be classified as magmatic zircons. Type II zircons exhibit dark coloration, fine grain sizes, poorly developed oscillatory zonation, and elevated contents of Th, U, and REEs. They contain few inclusions and have weak LREE and HREE fractionation, consistent with typical hydrothermal zircon. Zircon U-Pb dating results yield an age of 318.8 ± 4.0 Ma for the magmatic zircons, representing the magmatic crystallization age of the graphite-bearing alkaline granite. Hydrothermal zircons have two age groups: One is 299.9 ± 4.6 Ma, which is close to the age of the fine-grained biotite granite, the latest lithoface associated with graphite mineralization. It might be derived from magmatic hydrothermal fluids, representing the graphite mineralization age. The other is 259.9 ± 3.3Ma, which is obviously later than the age of the Huangyangshan pluton. It possibly related to late regional metamorphic fluids. The fine-grained biotite granite has significantly lower total REEs than other lithofacies of the Huangyangshan pluton, with an M-type tetrad effect in REE distribution. The M-type tetrad effect is the result of intense fluid activity, possibly directly related to hydrothermal graphite mineralization. Therefore, the ∼300 Ma hydrothermal event reflected by the first-stage hydrothermal zircons has a close genetic relationship with the fine-grained biotite granite. The Huangyangshan graphite mineralization has experienced a magmatic hydrothermal process and should be classified as a hydrothermal deposit.